Multi‐harmonic oscillation and stability analysis of double‐input buck/buck‐boost inverter. Issue 1 (30th December 2020) - Zhang, Hao; Liu, Wei; Ding, Honghui; Zheng, Feng
Abstract: In this study, multi‐harmonic oscillation behaviour and stability problem in double‐input buck/buck–boost inverter are investigated both theoretically and experimentally. First, the observer‐pattern model is obtained by the local orthogonal and autonomous transformation in order to eliminate the time‐variance effect from both fundamental component and the 'hidden' second‐harmonic in the double‐input cascade system. Based on the proposed model, bifurcation analysis method is employed to reveal the underlying mechanism of the multi‐harmonic oscillation behaviour and identify the dominant harmonics. It is shown that the occurrence of Hopf bifurcation results in the double‐adding harmonic oscillation, and the interaction between the double‐adding harmonic components and the 'hidden' second harmonic component is also responsible for the multi‐harmonic oscillation behaviour. Meanwhile, the occurrence of the multi‐harmonic oscillations leads to the decrease of the system efficiency. For stability enhancement, the harmonic‐stability sensitivity is presented to evaluate the influence of the key circuit parameters on the system stability quantitatively. In addition, the stability boundaries of the double‐input inverter for these key parameters are provided to guide the system optimal design. Finally, the effectiveness of the above analysis is verified by those experimental results.